A Study of the Author's Warning Against Resentment in Minority Literature in Virginia Woolf's A Room of One's Own - Meena, Madhu Kanta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Virginia Woolf's A Room of One's Own (1929) stands as a foundational text of feminist literary criticism, yet within its celebrated arguments for women's financial and intellectual independence lies a more nuanced psychological warning: the injunction against allowing resentment to corrupt artistic creation. This article examines Woolf's complex negotiation with anger, tracing her argument that while resentment is an inevitable response to patriarchal oppression, it must be transcended for literature to achieve its fullest expression. Through analysis of Woolf's contrasting evaluations of Charlotte Brontë and Jane Austen, her theory of the androgynous mind, and the critical responses from feminists of color who have engaged with her work, this study reveals both the power and the limitations of Woolf's warning. The article argues that Woolf's ambivalent treatment of resentment—simultaneously expressing it and warning against it—creates a productive tension that continues to inform discussions of minority literature and the politics of aesthetic expression.